BUSINESS STRATEGY FOR EXPANSION AND SUCCESSFUL DEVELOPMENT OF VITICULTURE. - Allakuliyev Guvanch (2021)
Grapes are one of the largest produced and traded products in the world. After 2000, the number of grapes produced and consumed in the world has increased dramatically. With the increase in supply, the demand for high-quality and trending grape varieties has grown. The goal of my work was to find ways to increase profits and expand the business for grape growing farmers. Farmers in our country Turkmenistan and Central Asia are less familiar with the trending grape varieties in the world. There is a lack of market research and analysis, a professional approach to the growing process, harvesting and supply chain. In this research, I analysed the growing export, import, production, and consumption markets. Choosing the right country for export and finding out what consumers prefer in this country that plays a big role in the success of grape exports. You must first create a business plan and make market analysis to determine the strengths and weaknesses. Set an end goal and develop a strategy to achieve the goal. Analyse the needs of the global market and offer a competitive product. Select the variety of grape for export. Select the country to export. Analyse the country by opportunities and disadvantages. Make a marketing plan to promote your product to a targeted audience and offer the product in an attractive way according to the consumers preference. It is necessary to take into account the importance of professionalism and training of employees. As the cultivation and export of fruit and vegetable products consists from a very long chain of processes, in case of failure with one step, the result will be lost of yield or product and all other waste is irrevocable. It is necessary to teach employees and observe very strictly all the following works for growing grapes as analysis and fertilization of the soil, the correct cultivation of seedlings, the correct watering, the correct fight against various diseases, the understanding of the importance of new technologies implementation for accurate and correct farming, the correct ripening and harvesting, the correct storage and transportation. For the development of viticulture, a state support program is very important. It is necessary to train farmers, create associations of winegrowers, ensure the availability of all necessaries for the cultivation of grapes, provide financial support and subsidies, reduce customs and taxes and support farmers for competitiveness of product in the global market.